2021
DOI: 10.2217/ijh-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload During the Treatment of Acute Leukemia: Pretransplant Transfusion Experience

Abstract: Background: Recent studies have shown the increased risk of mortality in cases with acute leukemia and iron overload. We aimed to determine the status of iron overload in patients with acute leukemia. Materials & Methods: Patients diagnosed with acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) between January 2015 and December 2019 were included in the study. Results: At 6 months, there were statistically more patients with serum ferritin >1000 in the AML group compared to the ALL gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Several studies showed the increased level of serum ferritin among patients diagnosed with leukemia during early and late stages and, after the cessation of treatment. [17][18][19][20][21][22][23] Importantly, a significant proportion of patients (33.3%) exhibited serum ferritin levels above the threshold of 1000 ng/ mL, which is considered indicative of iron overload. This observation further supports the association between leukemia and elevated ferritin levels, suggesting a dysregulation in iron metabolism during the disease course.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies showed the increased level of serum ferritin among patients diagnosed with leukemia during early and late stages and, after the cessation of treatment. [17][18][19][20][21][22][23] Importantly, a significant proportion of patients (33.3%) exhibited serum ferritin levels above the threshold of 1000 ng/ mL, which is considered indicative of iron overload. This observation further supports the association between leukemia and elevated ferritin levels, suggesting a dysregulation in iron metabolism during the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, certain studies have examined the correlation between erythrocyte transfusions and iron overload in patients with leukemia. Yokus et al 22 reported an increased risk of hepatic and endocrine dysfunction in children with leukemia who had received 10 or more units of red blood cell transfusions. Another study by Acar and colleagues focused on evaluating liver iron content (LIC) using MRI in children with ALL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations